P026 Do maternal and paternal cognitions and sleep-related practices relating to their own and their child's sleep predict their child's parentally reported and actigraphically assessed sleep?. (19th November 2019) - Cook, Georgia; Appleton, Jane V; Wiggs, Luci
Abstract : Introduction: Various factors have been linked to child sleeplessness problems (CSP). These include parental cognitions about child sleep and bedtime behaviours parents use with their child. However, previous research has predominantly focused on mothers and how both parents think and behave in relation to their own sleep and broader sleep-related practices may also be important. The current study aimed to explore whether maternal and paternal cognitions and sleep-related practices (relating to their own and their child's sleep) and bedtime behaviours used with their child predicted subjective and objectively assessed child sleep. Method: Mothers and fathers from 44 families (with a 12–24 month old child) completed questionnaires assessing their sleep-related cognitions and practices relating to their own and their child's sleep. Parent's provided details about their child's sleep (including if they perceived their child to have a CSP). Actigraphy and sleep diary data was collected on the child's sleep for 5 nights. Regression analyses were conducted to explore if parental cognitions and sleep-related practices (relating to their own and child's sleep) predicted perceptions of their child's sleep and the child's actual sleep. Results: Binary regression models predicting parental perception of a CSP, for both mothers and fathers, were significant. Specific and different bedtime behaviours used with their child were the only significant independent predictors of both maternal and paternal perceptions of a CSP. For mothers, use of physical comforting and for fathers settling by encouraging autonomy and using movement were significant predictors. A hierarchical linear regression to predict objective child sleep from maternal and paternal variables was not significant. Discussion: Use of different bedtime behaviours were related to mothers' and fathers' perceptions of CSP. Additional research is required to elucidate the reason for apparent differences between parents; perhaps mothers and fathers find different types of settling methods more acceptable or undesirable?